2015
DOI: 10.4314/gjass.v14i1.5
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of improved rubber production technologies by farmers in Akwa Ibom state, Nigeria

Abstract: This study examined the adoption of improved rubber production technologies by farmers in Akwa Ibom State, Nigeria. The specific objectives of the study are to; identify improved rubber production technologies disseminated to farmers, identify methods for disseminating information on improved rubber production technologies, determine levels of adoption of improved rubber production technologies and finally to determine effects of adoption of improved rubber production technologies on income of farmers in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 1 publication
3
18
0
Order By: Relevance
“…The implication of this finding is that cassava production in the area was largely carried out by the women. This finding agreed with the findings of Effiong and Effiong (2015) that, women farmers in Akwa Ibom State are largely involved in food crop production. The table also, showed that majority of the respondents were married (68.99%).…”
Section: Socio-economic Characteristics Of Respondentssupporting
confidence: 92%
See 1 more Smart Citation
“…The implication of this finding is that cassava production in the area was largely carried out by the women. This finding agreed with the findings of Effiong and Effiong (2015) that, women farmers in Akwa Ibom State are largely involved in food crop production. The table also, showed that majority of the respondents were married (68.99%).…”
Section: Socio-economic Characteristics Of Respondentssupporting
confidence: 92%
“…The study was conducted in (Effiong and Effiong, 2015). The population of the study comprises all cassava farmers in the study area.…”
Section: Methodsmentioning
confidence: 99%
“…Vegetables play important roles in human body especially those concerning essential vitamins and mineral elements, thus, resulting in the prevention of the problem of malnutrition. Effiong, Ijioma and Effiong (2016) and FAO (2010) pointed out that the problem of malnutrition is mostly escalated among children and pregnant women, and is responsible for high mortality rates of these groups. Insufficient consumption of vegetables annually cause about 2.1 million deaths worldwide, and is one of the top ten risk factors contributing to human mortality (Effiong, Effiong and Udo, 2015;Effiong and Aboh, 2019;Prescott-Allen andPrescott-Allen, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The intercrops are fluted pumpkin, melon, sweet yam, cocoa yam, and water yam. Apart from farming, they are also engaged in palm wine tapping, welding works, processing of wild palm fruits, tailoring, trading and processing of cassava into garri for sale and consumption (Effiong and Asikong, 2013;Effiong, Ijioma and Effiong, 2016). Descriptive survey was adopted for this study.…”
Section: Introductionmentioning
confidence: 99%
“…Nigeria has a history of rich agricultural development dating back to the precolonial era, the 1960s and the first Republic of 1960-1966 where regional agriculture with specialization in the cultivation of selected crops such as rubber, cocoa and oil palm in the various regions were practiced (Effiong and Aboh, 2018). The earnings from the agricultural sector were used in financing major developmental projects and programmes in the country, notable amongst many were the University of Lagos, the Obafemi Awolowo University Ile-Ife, Osun State, the 26-storey cocoa house in Ibadan Oyo State and the Free Education Programme in the Western Region; all financed from the proceeds of cocoa by the then premier government (Ekong, 2010;Effiong and Effiong, 2015).…”
Section: Introductionmentioning
confidence: 99%